STUDI EKSPLORASI PEMBIAYAAN USAHA KECIL DAN MENENGAH (UKM) DI SENTRA-SENTRA INDUSTRI KECIL DI JAWA TIMUR - Siswanto, Ely (IQTISHODUNA, 2011)
This research tried to explore and describe the opinion and preference of small and medium enterprises around the financing supervisory in centers of SMEs in East Java. The good description in financing and financial supervisory models would be the basic for determining the best formulation in financing and financial supervisory programs. Small and medium enterprises (SMEs) in Indonesia are developed in centers of small and medium enterprises (sentra UKM) to supervisory efectively. The centers of SMEs in this research involved Sentra Industri Mebel Kayu Pasuruan, Sentra Industri Tempe Malang, Sentra Industri Kerajinan Perak Lumajang and Sentra Industri Sandal Sepatu Mojokerto. The result of this research indicating the need for financing and financial supervisory which accommodate non financial development such as marketing, technology, and management. Furthermore, exploratory for this research indicated that there are financing and financial supervisory established in the centers known as MAP model.